MK-STYX Alters the Morphology of Primary Neurons, and Outgrowths in MK-STYX Overexpressing PC-12 Cells Develop a Neuronal Phenotype - Banks, Dallas A.; Dahal, Arya; McFarland, Alexander G.; Flowers, Brittany M.; Stephens, Christina A.; Swack, Benjamin; Gugssa, Ayele; Anderson, Winston A.; Hinton, Shantá D. (Frontiers in Molecular Biosciences, 2017)
We previously reported that the pseudophosphatase MK-STYX (mitogen activated kinase phosphoserine/threonine/tyrosine binding protein) dramatically increases the number of what appeared to be primary neurites in rat pheochromocytoma (PC-12) cells; however, the question remained whether these MK-STYX-induced outgrowths were bona fide neurites, and formed synapses. Here, we report that microtubules and microfilaments, components of the cytoskeleton that are involved in the formation of neurites, are present in MK-STYX-induced outgrowths. In addition, in response to nerve growth factor (NGF), MK-STYX-expressing cells produced more growth cones than non-MK-STYX-expressing cells, further supporting a model in which MK-STYX has a role in actin signaling. Furthermore, immunoblot analysis demonstrates that MK-STYX modulates actin expression. Transmission electron microscopy confirmed that MK-STYX-induced neurites form synapses. To determine whether these MK-STYX-induced neurites have pre-synaptic or post-synaptic properties, we used classical markers for axons and dendrites, Tau-1 and MAP2 (microtubule associated protein 2), respectively. MK-STYX induced neurites were dopaminergic and expression of both Tau-1 and MAP2 suggests that they have both axonal and dendritic properties. Further studies in rat hippocampal primary neurons demonstrated that MK-STYX altered their morphology. A significant number of primary neurons in the presence of MK-STYX had more than the normal number of primary neurites. Our data illustrate the novel findings that MK-STYX induces outgrowths in PC-12 cells that fit the criteria for neurites, have a greater number of growth cones, form synapses, and have pre-synaptic and post-synaptic properties. It also highlights that the pseudophosphatase MK-STYX significantly alters the morphology of primary neurons. Key Findings 1. MK-STYX significantly increases the number of primary neurites in PC-12 cells. 2. MK-STYX-induced neurites exhibit growth cones and small actin protrusions. 3. MK-STYX modulates actin expression. 4. MK-STYX induced neurites form synapses. 5. MK-STYX-induced neurites form pre-synaptic and post-synaptic processes. 6. MK-STYX alters the morphology of hippocampal primary neurons. 7. MK-STYX increases the number of neurites in primary hippocampal neurons.